ANALISIS KINERJA ANGGOTA MGMP IPA SMP KOTA PEKANBARU DALAM PENGEMBANGAN PROFESI - Fatmala, Kiki; Suryawati, Evi; ', Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this study was to describe performance of the of Junior High School science MGMP’s members in Pekanbaru on profession development. This study held on November 2016 until April 2017. The sample of this study was 50 person science MGMP’s members of Junior High School in Pekanbaru that selected by their activeness in following the MGMP’s activities. This study conducted with closed-ended and open–ended questionnaire. The closed-ended questionnaire consist of 30 items and divided into 4 indicator. The indicator are motivation, creativities, self efficacy and attitude, and 5 open-ended questionnaire as supporting data. The whole item questionnaire enclosed declared valid and reliable. Closed questionnaire of teachers performance was tested through Pearson correlation test, where all items declared valid. Reliability test through Cronbach's alpha test, was obtained 0.896 and showed the good criteria. Validity and reliability test were analyzed using SPSS (Statistical Package for Social Studies) version 18.00 for Windows. Data were analyzed descriptively. The result, the performance of science MGMP’s members Senior High School in Pekanbaru in profession development showed good criteria with 4,07 in average, which details as follows: Motivation showed good criteria with 4,02 in average, creativity showed good criterion with 3,90 in average, self efficacy showed good criterion with 4,09 in average, and attitude showed very good criterion 4,29 in average. Finally, it is known that the performance of Junior High School science MGMP’s members in Pekanbaru in profession development is being good on category.Key words: Teacher’s Performance, MGMP’s science, teacher profession.